Diagnostic Challenge of a Deep Minor Salivary Gland Neoplasm. (6th June 2014) - Wagner, Vivian P.; Martins, Manoela D.; Genari, Bruna; do Amaral, Fernando B.; Maciel, Antônio C.; Martins, Marco A. T.; Munerato, Maria C.
Abstract : Core needle biopsy represents a safe and cheap alternative diagnostic method to open biopsy and fine-needle aspiration cytology in head and neck tumors. There is little evidence in the literature about the use of core needle biopsy in minor salivary gland lesions. This single case report presents a 60-year-old woman with a painless swelling in the soft palate, breathing and swallowing difficulties, and a feeling of suffocation. Two open biopsies had inconclusive diagnosis and the lesion could only be assessed and diagnosed as pleomorphic adenoma through core needle biopsy. Recognizing the correct indication of core needle biopsy can benefit both health professionals and patients; thus, it is important to consider the possibility of performing this method to diagnose minor salivary gland tumors.